SOSIALISASI POLA HIDUP BERSIH DAN SEHAT DALAM UPAYA PENCEGAHAN STUNTING DI DESA MANLETEN KABUPATEN BELU - Anselmus Boy Baunsele; Ambrosius Faofeto; Hildegardis Missa; Aloysius Djalo; Sardina Ndukang; Anggelinus Nadut; Gerardus D. Tukan; Maximus M. Taek; Adri Gabriel Sooai (Politeknik Negeri Sriwijaya, 2023)
The healty lifestyle is a habits that needs to be used as a principle of life by every people to improving the life quality especially for the health sector. The good comprehension of health can help every people for stunting prevention. Stunting is a kind of disease that caused by the poor nutrition of meals for the children for their growing period. By the community service program of public education of high nutrition food for the parents to increase the nutrition grade for these children is expected to prevent the potential for stunting in these children. In addition, this community service program give the new experience for the community to utilize the ingridients food to create the high nutrition food with low price and can produce in every household. Babanas and corn are abundantly available in Manleten Village and always consumed by the conventional processing can be produced to be a new variant of food that can be a new food reference